Improving Village Correspondence Services With An Open Access Repository System - Jandri M. Siban; Muhammad Imanullah; Khairullah; Harry Witriyono (Jurnal Komputer, Informasi dan Teknologi, 2025)
Village correspondence services are one of the important functions of village government in providing administrative services to the community. However, conventional systems that still rely on manual recording and physical storage often cause various obstacles such as slow processes, difficulties in searching archives, and minimal transparency in public services. This study aims to design and develop a web-based open access repository system to improve correspondence services in Muara Tiga Ilir Village, Kedurang District, South Bengkulu Regency. The research method used is Research and Development (R&D) with the stages of identifying potential problems, data collection, system design, design validation, design revision, product trials, and the final product. The developed system has key features such as admin login for access security, an admin dashboard as a control center, automatic input and creation of outgoing letters, uploading incoming and outgoing letters, searching for letters based on date ranges, and open access for the public to download the required letters. The test results show that the system is able to improve the efficiency of the correspondence process, reduce service time, increase transparency through open access, and facilitate digital archiving. The implementation of this system is expected to be a model for digital transformation of public services at the village level that supports the principles of good governance and smart villages. Black box testing functions as a whole and based on the results of questionnaire data processing, the average value in the pre-test stage of 81.75% (Agree category) increased to 86.70% (Strongly Agree category) in the post-test stage. This shows an increase of 4.95 % , which indicates that the tested system has experienced improvements and increased user satisfaction after implementation